Competitiveness and Entrepreneurship in Latin America - Hnyilicza, Esteban (2008)
This paper reviews the empirical evidence on the critical factors impinging on the success or failure of enterprise development policies in Latin America. Guidelines are proposed to integrate novel initiatives into a coherent strategy for entrepreneurship development. The proposed approach encompasses four building-blocks: incubators, entrepreneur development, business development services, and incentive mechanisms to promote cooperative behavior. The notion that entrepreneurial development is one of the key links in the transmission mechanisms between the conception stage and the implementation phase of competitiveness policies is stressed.